1991
DOI: 10.1128/aac.35.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia prolongs the aminoglycoside-induced postantibiotic effect in Pseudomonas aeruginosa

Abstract: The objective of this study was to determine whether hyperoxia enhances aminoglycoside activity against Pseudomonas aeruginosa. The existence of tobramycin-oxygen synergy was determined by using the in vitro postantibiotic effect (PAE). P. aeruginosa strains were incubated for 1 h in medium containing tobramycin at four times the MIC in the following gas mixtures: normoxia (21% 02), hyperoxia (100% 02 101.3 kPa), or hyperbaric oxygen (100% 02, 274.5 kPa). Tobramycin was removed after 1 h and bacteria were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 31 publications
(28 reference statements)
0
25
0
2
Order By: Relevance
“…Whatever the precise mechanism, the time for recovery from tobramycin exposure to control values for crude protein synthesis, 13-galactosidase activity, cell morphology, and DNA complexity are correlated with one another and with the standard definition of the PAE (9). The PAE associated with aminoglycoside therapy has been incorporated into theories regarding optimal dosing regimens (10,19,20,28,29,33,35). The results presented in this study suggest that the PAE provides a reasonable basis for allowing aminoglycoside concentrations to fall below detectable limits for a portion of the dosing interval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the precise mechanism, the time for recovery from tobramycin exposure to control values for crude protein synthesis, 13-galactosidase activity, cell morphology, and DNA complexity are correlated with one another and with the standard definition of the PAE (9). The PAE associated with aminoglycoside therapy has been incorporated into theories regarding optimal dosing regimens (10,19,20,28,29,33,35). The results presented in this study suggest that the PAE provides a reasonable basis for allowing aminoglycoside concentrations to fall below detectable limits for a portion of the dosing interval.…”
Section: Methodsmentioning
confidence: 99%
“…that DNA synthesis was inhibited in E. coli transiently exposed to gentamicin at low multiples of the MIC in Mueller-Hinton broth during the PAE (13). Another study using pulse-chase [35S]methionine labelling suggested that protein synthesis inhibition immediately after tobramycin exposure might be correlated with the duration of PAE (28). We examined the effects of transient in vitro exposure to tobramycin on macromolecular synthesis in a clinical isolate of E. coli in order to correlate the molecular mechanism of action of tobramycin with the observed PAE.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no evidence that hyperoxia acts synergistically with protein synthesis inhibitors through free radical mechanisms to inhibit bacterial growth after a short antibiotic exposure. It appears more likely that the synergistic effects of hyperoxia with antimicrobial agents that are protein synthesis inhibitors (18) are mediated by an inhibitory effect of hyperoxia on protein synthesis.…”
mentioning
confidence: 99%
“…We exposed bacteria to hyperoxia (for 1 or 18 h) before examining the PAE to determine whether increased antiox- (18). e Significantly different from data for bacteria under normoxic conditions (P < 0.01).…”
mentioning
confidence: 99%
See 1 more Smart Citation